The Mental Health Impacts of COVID-19 on PK-12 Students: A Systematic Review of Emerging Literature - David Naff; Shenita Williams; Jenna Furman-Darby; Melissa Yeung (SAGE Publishing, 2022)
The mental health impact of the coronavirus disease 2019 (COVID-19) pandemic on PK-12 youth is likely an urgent and enduring concern, yet research on this topic is still emerging. To synthesize current knowledge, the researchers conducted a systematic review of empirical studies exploring the mental health impacts of COVID-19. Five themes emerged across 104 included studies: (a) the pandemic proved widely disruptive to PK-12 youth; (b) there was a clear connection between the mental health of caregivers (e.g., parents) and children; (c) the pandemic broadly increased levels of stress, anxiety, and depression in PK-12 youth; (d) students were particularly affected on the basis of age, gender, race/ethnicity, socioeconomic status, and previous mental health or disability diagnosis; and (e) youth demonstrated negative and positive coping strategies and even saw some positive mental health outcomes during the pandemic. Implications for research, practice, and policy are discussed.